Lower extremity gangrene in children from traditional bone setters care: an avoidable cause of limb loss - Echem, Richard C.; Eyimina, Phillip D. (International Journal of Research in Medical Sciences, 2020)
Background: Worldwide, lower extremity gangrene in children is rare. In orthopaedic practice in developing countries, a frequent cause of extremity gangrene is the practice of traditional bone setting. Aim of the study was to document lower extremity gangrene in children resulting from the care of traditional bone setters’ as seen in a tertiary health institution. Methods: A prospective study of children presenting with lower extremity gangrene from the care of traditional bone setters at the University of Port Harcourt Teaching Hospital from January 2006 to December 2018. Data obtained included the patients socio-demographics and relevant information related to the diagnosis. Data was analysed with SPSS version 20. Results: Eighteen children with lower extremity gangrene were seen. Their ages ranged from 10 days to 132 months. There was a female preponderance. Their parents mostly had primary and secondary levels of education and majority were married. The most common diagnosis was tibiofibular fractures followed by congenital clubfoot. Trauma-related injuries were mostly from falls. Duration before presentation ranged from 7 to 28 days. Majority had massage, splinting and bandaging from the bone setter. Most common associated complication at presentation was sepsis. All had provisional amputation. Most common amputation was below knee. Most had stump refashioning within 15 days. One had split skin grafting. There was one mortality. Duration of hospital stay ranged from 3 to 65 days. Conclusions: Children at any age can develop lower extremity gangrene from traditional bone setters’ care. This is an avoidable and preventable sequelae of care. Parental health education is necessary to discourage their patronizing traditional bone setters.